2014
DOI: 10.1016/j.jcin.2014.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Fractional Flow Reserve Calculation From 3-Dimensional Quantitative Coronary Angiography and TIMI Frame Count

Abstract: Computation of FFRQCA is a novel method that allows the assessment of the functional significance of intermediate stenosis. It may emerge as a safe, efficient, and cost-reducing tool for evaluation of coronary stenosis severity during diagnostic angiography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
147
1
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 310 publications
(152 citation statements)
references
References 18 publications
2
147
1
2
Order By: Relevance
“…12,13 Recently, 3-dimensional (3D) quantitative coronary angiography (QCA)-based FFR evaluation (FFR QCA ) proved to be a promising tool for evaluating the functional significance of intermediate coronary stenosis during diagnostic coronary angiography. 14 The objective of this study was to present a new approach for estimating invasive FFR using OCT lumen contour-based 3D coronary models (FFR OCT ) and CFD algorithms. In addition, the clinical usefulness of FFR OCT was evaluated with pressure wire-based FFR in patients with ambiguous intermediate diameter stenosis in the left anterior descending artery.…”
mentioning
confidence: 99%
“…12,13 Recently, 3-dimensional (3D) quantitative coronary angiography (QCA)-based FFR evaluation (FFR QCA ) proved to be a promising tool for evaluating the functional significance of intermediate coronary stenosis during diagnostic coronary angiography. 14 The objective of this study was to present a new approach for estimating invasive FFR using OCT lumen contour-based 3D coronary models (FFR OCT ) and CFD algorithms. In addition, the clinical usefulness of FFR OCT was evaluated with pressure wire-based FFR in patients with ambiguous intermediate diameter stenosis in the left anterior descending artery.…”
mentioning
confidence: 99%
“…6 QFR showed a direct correlation (r=0.81, P<0.001) and good agreement (mean difference: 0.00±0.06, P=0.541) with FFR. 6 The accuracy of QFR for predicting FFR ≤0.80 was 88%, with positive and negative predictive values of 82% and 91%, respectively. 6 In addition, subsequent studies showed that QFR (i.e., fQFR, cQFR and adenosine-flow QFR [measured hyperemic flow velocity derived from angiography during adenosine-induced descending (LAD) coronary artery did not alter the results for the diagnostic performance of QFR ≤0.80 for predicting FFR ≤0.80 (Table 4).…”
Section: Qfr Vs Ffrmentioning
confidence: 91%
“…Recent studies have demonstrated good correlation between QFR and FFR. [6][7][8] Mismatch between angiographic diameter stenosis and FFR is often observed in prior myocardial infarction (MI)-the coronary artery with the most severe stenotic lesion as the target vessel. Prior MI was defined by the following criteria: (1) …”
Section: Study Populationmentioning
confidence: 99%
“…Recently, high-resolution OCT imaging has been used to calculate coronary hemodynamics in image-based simulation models [610]. In these studies, the local region of interest (ROI) of the coronary artery, scanned using OCT, was merged into a rough 3D coronary arterial model reconstructed from biplane CAG images [1014].…”
Section: Introductionmentioning
confidence: 99%